Communities and conflict in early modern Colmar 1575 - 1730 - Wallace, Peter G. (Studies in German histories, 1995)
From 1575 to 1730, the citizens of the Alsatian Imperial city of Colmar were divided between Protestant and Catholic communities, plagued by chronic warfare, and ultimately subjugated by the kingdom of France. Drawing on a rich collection of serial archival sources, Wallace reconstructs the collective biography of 6,700 civic officials, merchants, artisans, and agricultural workers in order to examine the local impact of confessionalization in a religiously mixed town, the effect of warfare on the economic interdependence of town and country, and the tensions between French absolutism and traditional civic political culture. Economic historians, scholars of the Reformation, and students of French and German history will find many valuable insights in this multifaceted analysis.